Quantification of the Therapeutic Antibody Ocrelizumab in Mouse Brain Interstitial Fluid Using Cerebral Open Flow Microperfusion and Simultaneous Monitoring of the Blood-Brain Barrier Integrity - Thomas Altendorfer-Kroath; Joanna Hummer; Denise Kollmann; Beate Boulgaropoulos; Reingard Raml; Thomas Birngruber (MDPI AG, 2023)
The increasing relevance of improved therapeutic monoclonal antibodies (mAbs) to treat neurodegenerative diseases has strengthened the need to reliably measure their brain pharmacokinetic (PK) profiles. The aim of this study was, therefore, to absolutely quantify the therapeutic antibody ocrelizumab (OCR) as a model antibody in mouse brain interstitial fluid (ISF), and to record its PK profile by using cerebral open flow microperfusion (cOFM). Further, to monitor the blood-brain barrier (BBB) integrity using an endogenous antibody with a similar molecular size as OCR. The study was conducted on 13 male mice. Direct and absolute OCR quantification was performed with cOFM in combination with zero flow rate, and subsequent bioanalysis of the obtained cerebral ISF samples. For PK profile recording, cerebral ISF samples were collected bi-hourly, and brain tissue and plasma were collected once at the end of the sampling period. The BBB integrity was monitored during the entire PK profile recording by using endogenous mouse immunoglobulin G1. We directly and absolutely quantified OCR and recorded its brain PK profile over 96 h. The BBB remained intact during the PK profile recording. The resulting data provide the basis for reliable PK assessment of therapeutic antibodies in the brain thus favoring the further development of therapeutic monoclonal antibodies.